2012
DOI: 10.1136/annrheumdis-2011-201009
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic symptoms are common and are associated with overall symptom burden and disease activity in primary Sjögren's syndrome

Abstract: ObjectivesTo determine the prevalence of autonomic dysfunction (dysautonomia) among patients with primary Sjögren's syndrome (PSS) and the relationships between dysautonomia and other clinical features of PSS.MethodsMulticentre, prospective, cross-sectional study of a UK cohort of 317 patients with clinically well-characterised PSS. Symptoms of autonomic dysfunction were assessed using a validated instrument, the Composite Autonomic Symptom Scale (COMPASS). The data were compared with an age- and sex-matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 40 publications
7
43
0
3
Order By: Relevance
“…Renal involvement is rare, occurring in less than 10% of cases [16] and most commonly involving renal tubular acidosis. Autonomic symptoms may affect 50% of individuals with SS [17]. Clinical pulmonary involvement occurs in 20-30% of patients with SS and is associated with a four-fold increase in 10-year mortality [18].…”
Section: Clinical Manifestations Of Ssmentioning
confidence: 99%
“…Renal involvement is rare, occurring in less than 10% of cases [16] and most commonly involving renal tubular acidosis. Autonomic symptoms may affect 50% of individuals with SS [17]. Clinical pulmonary involvement occurs in 20-30% of patients with SS and is associated with a four-fold increase in 10-year mortality [18].…”
Section: Clinical Manifestations Of Ssmentioning
confidence: 99%
“…4 The association of autonomic dysfunction and primary Sjö gren's syndrome has been established in previous studies. 5 Newton et al's 2012 study of 317 patients with primary Sjögren's syndrome demonstrated a 55% prevalence of dysautonomia, predominantly orthostatic hypotension. 5 However, very few cases of tonic pupils have been reported in Sjö gren's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…5 Newton et al's 2012 study of 317 patients with primary Sjögren's syndrome demonstrated a 55% prevalence of dysautonomia, predominantly orthostatic hypotension. 5 However, very few cases of tonic pupils have been reported in Sjö gren's syndrome. 4,[6][7][8][9][10][11][12] Our cases demonstrate bilateral tonic pupils as the initial manifestation of Sjö gren's-associated autonomic neuropathy/neuronopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Większość badaczy zgadza się ze stwierdzeniem, że przeciwciała przeciw receptorowi muskarynowemu typu 3 dla acetylocholiny są odpowiedzialne za zaburzenia prawidłowego funkcjonowania autonomicznego układu nerwowego, a zwłaszcza części przywspółczulnej u chorych z PSS [20].…”
Section: Patogeneza Neuropatii W Pierwotnym Zespole Sjögrenaunclassified
“…Ten ostatni objaw jest spowodowany zapaleniem neuronów zwoju rzęskowego [29]. Wykazano ponadto, że dysfunkcja układu autonomicznego [20]. Leczenie jest zwykle objawowe; jeśli przebiega z innymi typami neuropatii, stosuje się leczenie skojarzone, które jest wskazane w danym typie uszkodzenia obwodowego układu nerwowego.…”
Section: E Neuropatie Autonomiczneunclassified